2021
DOI: 10.13057/biodiv/d221051
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of endophytic fungi from the root bark of Syzygium zeylanicum, and the antibacterial activity of fungal extracts, and secondary metabolite

Abstract: Abstract. Syarifah, Elfita, Widjajanti H, Setiawan A, Kurniawati AR. 2021. Diversity of endophytic fungi from the root bark of Syzygium zeylanicum, and the antibacterial activity of fungal extracts, and secondary metabolite. Biodiversitas 22: 4572-4582. The decoction of the root bark of Syzygium zeylanicum has been used as traditional medicine, such as for treating pathogenic bacterial infections. Endophytic fungi that live in medicinal plant tissues have a high species diversity and biological activities corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Compound 223 was found to be active against S. typhi, E. coli, and B. subtilis with MIC values of 64 g/mL. p-Hydroxybenzaldehyde was also reported from Syzygium zeylanicum [110].…”
Section: Penicilliummentioning
confidence: 94%
“…Compound 223 was found to be active against S. typhi, E. coli, and B. subtilis with MIC values of 64 g/mL. p-Hydroxybenzaldehyde was also reported from Syzygium zeylanicum [110].…”
Section: Penicilliummentioning
confidence: 94%
“…Analysis showed that some isolates showed a nity for speci c tissues. There was no common genus of endophytes from the bark of leaves and stems, but the genus Trichoderma was found in the bark of the roots of S zeylanicum (Syarifah et al, 2021) . Some isolated endophytic taxa prefer a particular tissue type.…”
Section: Endophytic Fungi Diversity Analysismentioning
confidence: 99%
“…The diameter of the inhibition zone formed was measured with a caliper. The criteria for determining the antibacterial activity of the test sample and the diameter of the inhibition zone were determined by the following formula (El ta et al, 2019;Syarifah et al, 2021):…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ascorbic acid was used as a positive control, and DPPH in ethanol was used as a blank. Using equation 1, the absorbance obtained from the instrument was used to calculate the percentage inhibition (Syarifah et al, 2021) .…”
Section: Antioxidant Activity Test Using Dpph (22-diphenyl-mentioning
confidence: 99%